PENGARUH KOMPETENSI INSTRUKTUR, DAN KESADARAN HIDUP SEHAT SERTA FASILITAS TERHADAP MOTIVASI MASYARAKAT BEROLAHRAGA SENAM AEROBIC DI KOTA PAYAKUMBUH - Edra; Elsandra, Yesi (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
Sport is a basic need to maintain good physical condition and health, and plays an important role in national development. Law Number 11 of 2022 concerning Sports emphasizes the importance of educational sports, performance sports and recreational sports. One form of recreational sport that is popular in Payakumbuh City is Aerobiks, which is not only popular for fitness but also as a recreational activity. This research aims to analyze the influence of people's motivation to exercise Aerobiks in Payakumbuh City, with a focus on instructor competence, awareness of healthy living, and sports facilities. The population in this research is the people of Payakumbuh City. This research uses quantitative methods with primary data in the form of a questionnaire with a total research sample of 60 respondents taken based on sampling techniques. The data analysis technique used is descriptive analysis and inferential statistical analysis with Structural Equation Modeling (SEM) analysis of various Partial Least Square (PLS) variants. Measurement model or outer model, structural model test or inner model, and hypothesis testing with the help of Smart-PLS 4.0 software as a testing tool. The results of this research show that instructor competence and facilities have a significant effect on people's motivation to exercise Aerobiks in Payakumbuh City. Meanwhile, awareness of healthy living has no effect on people's motivation to exercise Aerobiks in Payakumbuh City.